Pelaksanaan Penyaluran Zakat Fitrah di Desa Sungai Simbar - Siti Nursiah; Risviyaldi Risviyaldi (AL-Muqayyad, 2022)
This study aims to determine the implementation of the distribution of zakat fitrah in Parit 05 Utara Sungai Simbar Village, Kateman District, Indragiri Hilir Regency. This type of research is field research with a qualitative descriptive method. Sampling using the Slovin formula with purposive sampling technique. With data collection methods using interviews, observation and documentation. The results of the study show that the distribution of zakat fitrah is carried out directly by all people who issue zakat fitrah. Zakat fitrah is handed over directly by muzakki to mustahik zakat. According to Islamic law, the implementation of the distribution of zakat fitrah is not entirely correct, because there are still muzakki who hand over their zakat fitrah to people who are not from the 8 asnaf zakat groups. In addition, mustahik zakat fitrah there get an inappropriate portion of zakat fitrah, namely poor mustahik receive less zakat fitrah than mustahik fisabilillah, even though Islam prioritizes the distribution of zakat fitrah to the needy and poor mustahik than other mustahik.